2013
DOI: 10.1155/2013/205714
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Tinnitus Loudness and Onset Duration with Audiological Profile Indicating Variation in Prognosis

Abstract: Purpose. Subjective tinnitus has different forms and degrees of severity. Many studies in the literature have assessed psychoacoustic characteristics of tinnitus but hardly any of them had focused on the association of audiological profile with onset duration and loudness perception. The aim of this study was to evaluate existence of any association between tinnitus loudness/onset duration and audiological profile to explain differences in prognosis. Method. Study design was prospective. The sample consisted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
6
1
Order By: Relevance
“…Mazurek et al (2010) also reported a significant correlation between mean PTA threshold at 0.5, 1, 2, 4, and 8 kHz and tinnitus loudness as measured with loudness matching (regression coefficient [r] 5 0.67, p , 0.0001). Gudwani et al (2013) likewise reported a significant correlation between tinnitus loudness as measured via loudness matching and average hearing thresholds at 0.5, 1, and 2 kHz. However, none of these studies examined whether the relationship between hearing loss and tinnitus loudness was associated with other variables known to influence tinnitus perception such as emotional states (Probst et al, 2016).…”
mentioning
confidence: 83%
“…Mazurek et al (2010) also reported a significant correlation between mean PTA threshold at 0.5, 1, 2, 4, and 8 kHz and tinnitus loudness as measured with loudness matching (regression coefficient [r] 5 0.67, p , 0.0001). Gudwani et al (2013) likewise reported a significant correlation between tinnitus loudness as measured via loudness matching and average hearing thresholds at 0.5, 1, and 2 kHz. However, none of these studies examined whether the relationship between hearing loss and tinnitus loudness was associated with other variables known to influence tinnitus perception such as emotional states (Probst et al, 2016).…”
mentioning
confidence: 83%
“…Sleep disturbance was rated on a 5-point scale as 0 ¼ never affected, 1 ¼ rarely affected, 2 ¼ sometimes affected, 3 ¼ mostly affected, and 4 ¼ always affected. 9,10 Clinical and audiological examinations consisted of: 1) audiological evaluation; 2) tinnitus psychoacoustic measures; 3) transient evoked otoacoustic emissions (TEOAE); and 4) GIN test.…”
Section: Methodsmentioning
confidence: 99%
“…Similar alterations were reported by Rybalko and Syka [ 25 ] when studying noise-induced tinnitus in rats. On the other hand, Gudwani et al [ 17 ] found that Na and Pa wave amplitudes were more than 90% normal in individuals with tinnitus. Interestingly, Theodoroff et al [ 16 ] suggested that the MLAEP protocol used is not specific enough to detect neurophysiological abnormalities associated with tinnitus, which may explain some of the different findings between these studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, these previous studies using MLAEP [ 10 , 11 , 16 , 17 ] used heterogeneous groups of individuals with tinnitus and yielded controversial results that need to be reconciled. An important aspect to consider regarding tinnitus is that it may also be caused by various diseases that affect different structures along the auditory pathway.…”
Section: Introductionmentioning
confidence: 99%